Understanding the importance of experiential marketing regarding luxury fashion brands in digital era from the consumer viewpoint - Symeonidou, Christina (2017)
The purpose of this dissertation is to apply the concept of experiential marketing into luxury fashion brands and investigate the key role that brand experience plays in creating memorable events in digital era in which digital tools such as social media try to engage consumers emotionally by building interactions between the brand and the consumer and subsequently generate extraordinary experiences. This research question is interesting to be examined from the consumer perspective, as a lot of studies have been conducted from the managerial or strategic point of view. Thus, it is important to investigate this concept based on consumers’ accounts regarding their own experience with luxury brands. The theoretical background was built on key theories provided by Holbrook and Hirschman (1982), Pine and Gilmore (1998) and Schmitt (1999) regarding experiential marketing and the experience economy, while the concept of luxury brands was examined incorporating different perspectives provided by several authors. This thesis was conducted by employing qualitative individual in-depth, semi-structured interviews to examine participants’ perceptions, motivations and experiences concerning luxury brands. Thus, this is an empirical, exploratory study which relies on consumers’ narratives regarding luxury experiences. The sample that was employed was a purposive sample consisting of female participants. The data was effectively collected, analyzed, and reported by incorporating thematic analysis and the data analysis model developed by Miles and Huberman in 1994. The key findings elucidated that consumers perceive luxury products or brands as fashionable, high priced, authentic items evoking sensations, emotions and creating experiences. Therefore, consumers considered experiences to be of utmost importance in forging relationships with luxury brands of their choice concluding in luxury consumption. Additionally, consumers shared their opinions and beliefs concerning motivations and influences that have an impact on luxury consumption reporting as main influences peer pressure and promotional strategies, while the need to project their personality by creating their own self-image was highlighted as their main motivation. The data analysis illustrates that